Analisis Nilai Tambah dan Strategi Pengembangan Industri Keripi k Kentang Di PT Agro Lestari Merbabu Kecamatan Ngablak, Kabupaten Magelang: Added Value Analysis and Strategy of Potato Chip Business Development at PT Agro Lestari Merbabu Ngablak District, Magelang Regency - Dias Astuti (Universitas Widya Gama Mahakam, 2021)
Increasing business profits can be done through value added strategies and product development. The business development strategy is a long-term strategy for effective management by considering the strengths, weaknesses, opportunitie, and threats. The purpose of the study was to analyze the added value of potato chips products, to formulate internal and external factors that affect the potato chips business, and to formulate and determine the strategy for developing the potato chips business at PT Agro Lestari Merbabu. The research was conducted in March – April 2021, located in Magelang Regency. The research method used is a case study. Respondents amounted to 10 people consisting of internal parties and company stakeholders. The method of determining respondents using the purposive method. The research data were analyzed using descriptive analysis, added value, and SWOT analysis. Based on the results of the analysis, it can be seen that the Merbabu Potato Chips business produces an added value of IDR 20,533/kg and a value-added ratio of 52.65%. The potato chip business has main strengths in the form of an easy production process, the main weakness is that the company does not do much promotion, and there are 2 main opportunities in the form of regional conditions that support production activities and many tourist attractions as well as the main threat to slow market growth. The company's position in the IE matrix is ​​in cell V and it is better to hold and maintain. The priority strategy suggested for the Merbabu Potato Chips business is to market the product to tourist attractions at a relatively affordable and stable price.